Effects of Solid-Medium Type on Routine Identification of Bacterial Isolates by Use of Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry - Anderson, Neil W. (American Society for Microbiology, 2012)
Matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) is a rapid method for the identification of bacteria. Factors that may alter protein profiles, including growth conditions and presence of exogenous substances, could hinder identification. Bacterial isolates identified by conventional methods were grown on various media and identified using the MALDI Biotyper (Bruker Daltonics, Billerica, MA) using a direct smear method and an acid extraction method. Specimens included 23 Pseudomonas isolates grown on blood agar, Pseudocel (CET), and MacConkey agar (MAC); 20 Staphylococcus isolates grown on blood agar, colistin-nalidixic acid agar (CNA), and mannitol salt agar (MSA); and 25 enteric isolates grown on blood agar, xylose lysine deoxycholate agar (XLD), Hektoen enteric agar (HE), salmonella-shigella agar (SS), and MAC. For Pseudomonas spp., the identification rate to genus using the direct method was 83% from blood, 78% from MAC, and 94% from CET. For Staphylococcus isolates, the identification rate to genus using the direct method was 95% from blood, 75% from CNA, and 95% from MSA. For enteric isolates, the identification rate to genus using the direct method was 100% from blood, 100% from MAC, 100% from XLD, 92% from HE, and 87% from SS. Extraction enhanced identification rates. The direct method of MALDI-TOF analysis of bacteria from selective and differential media yields identifications of varied confidence. Notably, Staphylococci spp. from CNA exhibit low identification rates. Extraction enhances identification rates and is recommended for colonies from this medium.